2008
DOI: 10.1107/s160053680802477x
|View full text |Cite
|
Sign up to set email alerts
|

N-Methylisosalsoline from Hammada scoparia

Abstract: Key indicators: single-crystal X-ray study; T = 200 K; mean (C-C) = 0.001 Å; R factor = 0.033; wR factor = 0.089; data-to-parameter ratio = 23.0.The title compound (systematic name: 1,2-dimethyl-6-methoxy-1,2,3,4-tetrahydroisoquinolin-7-ol), C 12 H 17 NO 2 , is a major alkaloid isolated from Hammada scoparia leaves. It belongs to the isoquinoline family and it was characterized by NMR spectroscopy and X-ray crystallographic techniques. The absolute configuration could not be reliably determined. An intermolecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…Our results are in agreement with other works that indicated the richness of Haloxylon scoparium in alkaloids; Zerriouh and collaborators reported that the aerial part of Hammada scoparia collected in Algeria contains the alkaloids [39]. In addition, Jarraya and collaborators described the isolation and structural elucidation of N-methylisososaloline extracted from Haloxylon scoparium leaves collected in Tunisia [40].…”
Section: Phytochemical Screeningsupporting
confidence: 92%
“…Our results are in agreement with other works that indicated the richness of Haloxylon scoparium in alkaloids; Zerriouh and collaborators reported that the aerial part of Hammada scoparia collected in Algeria contains the alkaloids [39]. In addition, Jarraya and collaborators described the isolation and structural elucidation of N-methylisososaloline extracted from Haloxylon scoparium leaves collected in Tunisia [40].…”
Section: Phytochemical Screeningsupporting
confidence: 92%
“…The residue (5 g) was separated, on column chromatography over silica gel using a gradient of dichloromethane-methanol to give N-methylisosalsoline (545 mg) as white rosette crystals. The data of the 1 H-NMR spectra matched those reported in the literature [40].…”
Section: Extraction Of N-methylisosalsolinesupporting
confidence: 76%
“…In fact, the AE significantly boosted the antioxidant enzyme activities, which could be explained by the presence of many phenolic compounds having a potent antiradical activity in comparison with ascorbic acid and BHT. In fact, we previously isolated some phenolic alkaloids (N-methylisosalsoline, 1-methylisosalsolinol and dopamine) and flavonoids (quercetin, isorhamnetin and quercetin 3-O-robinobioside) from the AE of H. scoparia (Jarraya et al, 2005(Jarraya et al, , 2008. A new flavonol triglycoside, isorhamnetin 3-O-b-D-xylopyranosyl-(1 00 !3)-a-L-rhamnopyranosyl-(1!6 00 )-b-D-galactopyr anoside, has been isolated from the leaves of H. scoparia together with two known compounds, iso-rhamnetin3-O-b-D-apiofuranosyl-(1!2 00 )[a-L-rhamno pyranosyl-(1 00 !6 00 )]-b-D-galacto pyranoside and isorhamnetin 3-O-a-L-rhamnopyranosyl-(1!2 00 )[a-L-rha mnopyranosyl-(1 00 !6 00 )]-b-D-galactopyranoside (Ben Salah et al, 2002).…”
Section: Discussionmentioning
confidence: 99%